Evolved Gas Analysis and Kinetics of Catalytic and Non-Catalytic Pyrolysis of Microalgae Chlorella sp. Biomass With Ni/θ-Al2O3 Catalyst via Thermogravimetric Analysis - Wasif Farooq (Frontiers Media S.A., 2021)
This study investigates the efficacy of a prepared Ni/θ-Al2O3 catalyst during the pyrolytic conversion of Parachlorella kessleri HY-6 and compares the results with non-catalytic conversion. The catalyst was characterized by techniques such as Brunauer–Emmett–Teller (BET) for surface area, acidity, and X-ray powder diffraction (XRD). Isoconversional and combined kinetic methods were used to study the pyrolytic kinetics of the process. Ni/θ-Al2O3 was used at 10, 20, and 30% of the algal biomass. The addition of Ni/θ-Al2O3 facilitated the conversion by lowering the mean activation energy during pyrolysis. The catalytic effect was more pronounced at lower and higher conversions. The presence of the catalyst facilitated the pyrolysis as indicated by the lower value of activation energy and ∆H, and ∆G. Gases evolved during pyrolysis were qualitatively analyzed by FTIR to see the effect of catalyst on evolved gas composition during the pyrolysis process.